THE PROBLEM OF DEEP COMMUNICATION IN CONTEMPORARY ETHICS EDUCATION - Endro, Gunardi (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Contemporary developments in the fields Nanotechnology, Biotechnology, Information Technology and Cognitive Sciences (NBIC) have brought about industrial revolution 4.0 and society 5.0 which promises prospect of dramatic progress in human life but also risks complicated ethical issues and ethical dilemmas. It is therefore important to know how future generations will address these ethical problems and ethical dilemmas. Ethics education for Millennial and Generation Z is currently at stake as they will be the ones who will be involved in the development and application of those sciences and technologies. This research article aims to explore how the problem of declining deep communication essentially occurs in contemporary ethics education. To reach the aim, a traditional literature review in conjunction with qualitative meta-synthesis method was applied. The result shows that effective ethics education requires ethical discussions that take the form of deep communication to link its participants’ value systems. However, rapid development and frenzied use of digital information and communication technology (ICT) tend to influence Millennial and Generation Z more outward-oriented, accustomed to shallow communication, and eventually drown into weakened ability for deep communication. Recommendation to anticipate the problem is to intensively deploy creativity in using the digital information and communication technology (ICT) to provoke the emergence of the power of inward orientation through intrapersonal communication and self-reflection. To cite this article (7th APA style): Endro, G. (2022). The problem of deep communication in contemporary ethics education. Journal Communication Spectrum: Capturing New Perspectives in Communication, 12(1), 1-10. http://doi.org/10.36782/jcs.v12i1.2222